Integration and synchronization of external sensor data for a mobile robot - Takeuchi, E.; Tsubouchi, T.; Yuta, S. (SICE 2003 annual Conference (IEEE Cat. No.03TH8734) : 4-6 August 2003, 2003)
Integration of external sensory data is an important issue for mobile robotics. If the numbers of the sensors are increased, it must be better to integrate all the sensory data into unified data format. The idea of "unified sensory data bank" and modular architecture for sensing data processing are proposed in this paper. By the proposed software architecture, the robot could move through the free space around in the realistic environment.